First Aid Advisor / Wilhelmina Ngelambai - Wilhelmina, Ngelambai (2002)
This report is set out to discuss the development of intelligent system in medical domain. This report includes the introduction to the proposed system, the literature review, the methodology, system design, the development and implementation, testing and evaluation. The area of application is medical first aid. The report begins with the objectives and scope of the system. Literature review explores the structure of the intelligent system, the knowledge representation and techniques and also the existed intelligent system in medical domain. Case-based reasoning is a methodology that is proposed for knowledge acquisition for First Aid Advisor system. Visual Protog is the programming tool for the First Aid Advisor system. The system design shows the data flow of the proposed system. The development is focused on the knowledge engineering process. And testing is to debug the system and this is includes the maintenance. The evaluation is to measure the achievement of the system towards the desired performance.